(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Diarrhoea and dysentery remain prevalent health issues in many rural communities across Nigeria, often managed using traditional medicinal plants. This study documents an ethnobotanical survey conducted in the Anyigba Dekina Local Government Area (LGA) of Kogi State, Nigeria, aimed at identifying and cataloging plant species traditionally used for the management of diarrhoea and dysentery. Through interviews with 14 respondents, predominantly women and farmers, the study revealed a diverse array of medicinal plants utilized by the local community. A total of 52 plant species belonging to 29 families were recorded, with the Fabaceae and Asteraceae families being the most represented. Leaves were the most commonly used plant part, followed by whole plants, stem barks, and seeds. The documented species exhibited various growth habits, including trees, herbs, shrubs, climbers, and grasses. The study highlighted the prevalent methods of preparation, such as decoctions, infusions, juices, pastes, and topical applications, reflecting the rich traditional knowledge and practices associated with plant-based remedies in the region but also offers a foundation for further pharmacological investigations into the therapeutic potential of these plants.